Effect of adjuvant treatment with Xiyanping injection on the prognosis of viral encephalitis in children: a multicenter retrospective study - Tian, Wen; Chen, Yang; Liu, Huazhang; Wen, Danning; Wang, Zhe; Li, Ying; Liu, Li; Yang, Xiangna; Ma, Xueyan; Zhang, Yuanyuan; Ma, Chengjie; Wang, Rongbing; et al. (Frontiers in Pharmacology, 2025)
BackgroundViral encephalitis (VE), a central nervous system disorder with high mortality and disability rates, poses a serious threat to childhood development. Xiyanping injection (XYPI), an andrographolide sulfonate preparation widely used in China, exhibits anti-inflammatory, antiviral, antitumor, antibacterial and neuroprotective properties.MethodsWe conducted a retrospective study of 635 pediatric inpatients with VE who were hospitalized at seven medical centers in China between January 2015 and December 2021. Risk factors for poor prognosis were compared between inpatients treated with XYPI (n = 480) and those without XYPI treatment (n = 155). Propensity score matching was performed to reduce potential confounding. Clinical symptoms, hospitalization costs, complications and sequelae were evaluated simultaneously.ResultsMultivariate Logistic regression identified XYPI treatment as an independent protective factor for poor prognosis (odds ratio [OR] = 0.251, 95% confidence interval [CI]: 0.113–0.559, p < 0.001). XYPI significantly shortened the duration of fever and headache, reduced hospitalization costs, and lower the incidences of respiratory infections, myocardial injury, and sequelae (all p < 0.05).ConclusionAdjuvant XYPI therapy may improve clinical outcomes and reduce the economic burden in pediatric VE; however, randomized trials are warranted to validate these findings.